APLIKASI FUZZY MODEL TAHANI DALAM PENENTUAN PEMILIHAN SPESIFIKASI TABLET PC - YADNYA, I PUTU AGUS DARMAWAN DARMA; GANDHIADI, G.K.; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 8 No 2 (2019), 2019)
This study aimed to build a fuzzy database system of Tahani model in determining Tablet specification choices according to certain criterias that was inputted by user. The application of Tahani fuzzy model was developed by using PHP as the programming language and MySQL as database storage. The first step in developing this model was determining the input variables that were used in data searching process. After data had been inputted and the user had been choosing certain criteria, the membership degrees which were used in Tablet searching then would be calculated. The outcome of the search showed a list of Tablet which had a recommendation values greater than 0. It can be concluded that the system had been able to show the recommendation value in accordance of the inputted criterias.